Thinking through quality questioning : deepening student engagement - Walsh, Jackie A.; Sattes, Beth D. (Thousand Oaks, Calif : Corwin Press, 2011)
"This groundbreaking book provides teachers with an accessible, research-based blueprint for developing student meta-cognitive skills and ensuring that students take responsibility for their own learning. The authors use the findings of cognitive scientists to highlight quality questioning behaviors and explain how to apply them for improved student outcomes"-- Provided by publisher.
Includes index
Keywords: Inquiry-based learning; Active learning; Thought and thinking -- Study and teaching